Ecocritical Contemporaneity in Divakaruni’s The Palace of Illusions and Buddhisagar’s Karnali Blues - Pokhrel, Chet Bahadur (The Outlook: Journal of English Studies, 2026)
This article explores anthropocentrism, environmental ethics and biophilia in Chitra B. Divakaruni’s The Palace of Illusions and Buddhisagar’s Karnali Blues. With a focus on contemporaneity in both novels, the paper shows the global nature of environmental problems. It also highlights the urgency of environmental ethics. Divakaruni’s The Palace of Illusions is based on the epic, the Mahabharata. It negotiates the transactions between humans and nature. Similarly, Buddhisagar’s Karnali Blues reflects on human-nature interdependence and its consequences. Although the novels have been widely discussed from the perspectives of gender roles, myth and modernity, and memory and nostalgia, significant scholarly attention has not been given to ecocritical issues. Using a qualitative research approach, this study analyzes The Palace of Illusions and Karnali Blues from an ecocritical perspective. For the sake of analysis, the key ecocritical theorists, namely Cheryll Glotfelty, Greg Garrard, and J. Baird Callicott, have been used to critically interpret the novels. The findings emphasize that human beings deeply depend on environmental components. The study shows interconnectedness and biophilia in both novels. The article argues that despite anthropocentric activities, human beings must not forget environmental ethics. The study underscores the importance of the environment and the urgency of nature conservation. Finally, it concludes that human beings, for the sake of their own existence, must be ethically accountable to nature. To check for further apocalypses, the harmony between man and nature should be maintained.